(untitled) (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
Study prpose. This thesis aims to analyse the performance of the West Sumatra Provincial Liaison Agency in providing services to regional leaders. Materials and methods. This research uses a qualitative method with a descriptive design, a constructive interpretivism paradigm, and a literature review analysis. The theory used is Agus Dwiyanto’s performance theory, which states that performance indicators consist of productivity, service quality, responsiveness, responsibility, and accountability. Results. The performance of the West Sumatra Provincial Liaison Office in serving regional leaders is generally quite good. However, there are several areas that need improvement, such as the service quality indicator, where the Public Relations, Protocol, and Service Section does not yet have Standard Operating Procedures for serving regional leaders, the quantity and quality of human resources in the public relations section are still insufficient, there are limitations in the authority to publish news about regional leaders’ activities on the West Sumatra Provincial Government website, and the facilities and infrastructure supporting the performance of duties are still limited, and the budget planning is not yet mature. Meanwhile, the indicators of productivity, responsiveness, responsibility, and accountability are already functioning well. Therefore, the researcher’s recommendations are to establish Standard Operating Procedures for serving regional leaders, increase human resources in the public relations department, propose to the leadership that news coverage outside West Sumatra Province be delegated to the Liaison Office, propose the procurement of facilities and infrastructure to support leadership service activities, and develop a mature budget plan for leadership activities so that service to regional leaders can be maximised. Conclusion. The performance of the West Sumatra Provincial Liaison Office in providing services to regional leaders is generally satisfactory, particularly in terms of productivity, responsiveness, responsibility, and accountability. However, there are still challenges in the quality of services, such as the absence of SOPs, limited human resources and supporting facilities, and suboptimal budget planning. Improvement efforts have been made through the addition of personnel, the provision of facilities, and inter-agency coordination. To enhance performance in the future, it is necessary to establish SOPs, improve human resource quality, procure supporting equipment, and expand authority in the publication of regional leadership activities.